Predicting the potential distribution of Podophyllum hexandrum Royle in the Himalaya under CMIP6 climate projections - Zishan Ahmad Wani; P. P. Abdul Rahim; Javid Ahmad Dar; Aamir Nazir Lone; Sazada Siddiqui (Scientific Reports)
Abstract Podophyllum hexandrum is a globally endangered medicinal plant facing severe survival challenges. In the present study, habitat suitability modelling of P. hexandrum was carried out to identify potentially suitable habitats in the western Himalayas under current and future climatic scenarios using MaxEnt software. Future distribution modelling was carried out using Shared Socioeconomic Pathways; SSP126, SSP370 and SSP585 for the time period 2041–2070. MaxEnt output maps were categorized into four potential habitat suitability classes using threshold < 0.25 as “not suitable” 0.25–0.50 as “least suitable”, 0.51–0.75 as “moderately suitable”, and > 0.75 as “highly suitable”. Furthermore, overlay analysis was used to calculate loss, gain, and no change areas. Centroid migration direction and distance were also calculated. The model revealed that the precipitation amount of the driest month and mean annual air temperature determine the distribution of P. hexandrum. Under future climatic scenarios, the species is predicted to undergo significant changes in its distribution losing 8.12% and 8.25% of its suitable habitats under SSP370 and SSP585 pathways, respectively. Under SSP126 pathway, the species is predicted to gain an area of 1.63%. The species is predicted to shift southeastwards under all climatic scenarios and the distance of centroid migration will increase with an increased climate extremities. Though overlapping of its suitable habitats with Protected Areas plays an important role in conserving its wild populations. The decline in number of individuals due to habitat fragmentation, low rate of natural regeneration or seed germination and prolonged dormancy is still a serious concern. There is an urgent need to frame pertinent conservation and management policies for habitat restoration and reintroduction of this species, therefore, the present study will serve as a baseline in this direction.